Controle da vibração de transporte vertical considerando a aplicação de controle passivo e ativo - Gonçalves, Marcos (2022)
Considering the comfort of passengers in high-speed elevators, this work aims to present the study of the efficiency of passive control and active control in reducing vibration levels in a high-performance vertical transport system. To analyze the performance of the proposed controls, the horizontal response of a mathematical model of vertical transport with 4 degrees of freedom is considered, subject to excitations from the rail guide deformations. Being considered a passive control composed of a non-linear dynamic vibration absorber and an active control designed by a Proportional Integral Derivative (PID) control. The levels of vibration and comfort in the cabin, and the efficiency of the proposed control projects, are numerically analyzed considering the levels of lateral accelerations of the elevator with the levels of comfort felt by passengers in accordance with ISO 2631 and BS 6841. Numerical simulations demonstrated that the proposed PID control is efficient in reducing vibration levels and that the proper configuration of the non-linear dynamic vibration absorber parameters is essential to ensure a better level of comfort for passengers, and that the increase in speed associated with the use of the non-linear dynamic vibration absorber can improve the comfort level by reducing the accelerations in the elevator cabin.